Soybean Toxin (SBTX) Impairs Fungal Growth by Interfering with Molecular Transport, Carbohydrate/Amino Acid Metabolism and Drug/Stress Responses - Morais, Janne K. S.; Bader, Oliver; Weig, Michael; Oliveira, Jose Tadeu A.; Arantes, Mariana R.; Gomes, Valdirene M.; Da Cunha, Maura; Oliveira, Hermogenes D.; Sousa, Daniele O. B.; Lourencao, Andre L.; Vasconcelos, Ilka M. (PLOS ONE, 2013)
Soybean toxin (SBTX) is an antifungal protein from soybeans with broad inhibitory activity against the growth and filamentation of many fungi, including human and plant pathogenic species such as Candida albicans, Candida parapsilosis, Aspergillus niger, Penicillium herquei, Cercospora sojina and Cercospora kikuchii. Understanding the mechanism by which SBTX acts on fungi and yeasts may contribute to the design of novel antifungal drugs and/or the development of transgenic plants resistant to pathogens. To this end, the polymorphic yeast C. albicans was chosen as a model organism and changes in the gene expression profile of strain SC5314 upon exposure to SBTX were examined. Genes that were differentially regulated in the presence of SBTX were involved in glucose transport and starvation-associated stress responses as well as in the control of both the induction and repression of C. albicans hyphal formation. Transmission electron microscopy showed that C. albicans cells exposed to SBTX displayed severe signs of starvation and were heavily granulated. Our data were indicative of C. albicans cell starvation despite sufficient nutrient availability in the medium; therefore, it can be speculated that SBTX blocks nutrient uptake systems. Because neither the starvation signal nor the alkaline response pathway lead to the induction of hyphae, we hypothesise that conflicting signals are transmitted to the complex regulatory network controlling morphogenesis, eventually preventing the filamentation signal from reaching a significant threshold.